86 Ponseti technique for congenital talipes equinovarus – a physiotherapy led service. (30th November 2020) - Bowyer, Henry; Segaren, Neil; Dunkley, Mia; Parnell, Evette; Eastwood, Deborah
Abstract : Background: Congenital Talipes Equinovarus (CTEV) deformity affects 1:1000 new-borns. Since the Ponseti technique became popular, the need for operative intervention beyond tenotomy has reduced. However, mid-long term results remain poorly reported. This prospective case series describes our patient population and outcomes since 2011 with an innovative physiotherapy-led Ponseti service. Methods: A prospective study of CTEV patients attending the Ponseti clinic. Primary outcomes included range of movement, calf circumference and functional status. Parents of children over the age of 5 were asked to complete the Oxford Ankle Foot questionnaire (OxFAQ). Results: Between Feb 2011-Aug 2020, 75 (M=43) patients were treated. Mean age at follow-up was 87.5 months (range 18–157 m). 42 cases were bilateral and thus 117 feet were treated. 45 (60%) were idiopathic and 30 (40%) non-idiopathic. Of the 75 patients, 50 (67%) underwent tenotomy under local anaesthetic in clinic. Tenotomy rates were higher in non-idiopathic vs idiopathic patients (83% vs 56%)(P<0.002) Mean dorsiflexion (knee extended) in affected feet was 14°. In unilateral cases mean dorsiflexion (knee extended) in unaffected foot vs affected foot was 17° vs 12°. All idiopathic feet were plantigrade. Abnormal evertor function was seen in 3 of 66 (5%) idiopathic feet versus 22 of 51 non-idiopathic feet (43%) (p<0.0001). Calf circumference discrepancy was higher in unilateral cases versus bilateral (mean 1.3 cm versus 0.6 cm respectively). Unilateral cases undergoing tenotomy had a greater mean circumference difference (1.5 cm) versus those managed without tenotomy (0.7 cm). 43 idiopathic patients were suitable for OXFORD scoring at time of last review (i.e. older than 5 years old). The overall median OxFAQ was 96% with points lost only in the physical scale. Function in non-idiopathic cases was determined by their overall condition. Conclusion: The idiopathic club foot is well treated by a physiotherapy-delivered Ponseti technique with excellent outcomes at 5 yr follow-up both subjectively and objectively.